Blood Transfusion: A Risk Factor in Retinopathy of Prematurity (Bangladesh Journal of Child Health, 2012)
Background: Retinopathy of prematurity (ROP) is a retinal vascular disorder of preterm neonates resulting in visual impairement. Along with prematurity, very low birth weight and hyperoxia, role of blood transfusions in the occurrence of ROP has been strongly emphasized. Objective: To determine the relationship of timing and volume of blood transfusion and other factors with the development of ROP in preterm very low birth weight (VLBW) newborn infants. Methods: This was a prospective observational study. It was done among the premature (